Exploring the tribological behavior of Ti/Al-DLC/PAO/graphene oxide nanocomposite system. Issue 8 (15th April 2021) - Xu, Xiaowei; Guo, Peng; Li, Xiaowei; Lee, Kwang-Ryeol; Cui, Ping; Wang, Aiying
Abstract: The role of graphene oxide (GO) as an oil-based additive on the tribological behavior of Ti/Al-DLC films and its dependence on GO concentration were systematically investigated. The results revealed that, compared to the additive-free case, the system with a GO concentration of 0.003 wt% achieved remarkable friction reduction and wear resistance, which were decreased by 38.4% and 23.5%, respectively. This is attributed to the synergistic effect of tribo-induced graphitization and the adsorption of GO on the worn surface. However, when the GO concentration was further increased, it induced the clumping of the GO additive, causing increased friction coefficient and severe abrasive wear of the worn surface.